Postoperative Nausea and Vomiting: Validation of the Portuguese Version of the Postoperative Nausea and Vomiting Intensity Score - Veiga Dalila; Helder Pereira; Carlos Moreno; Clarisse Martinho; Cristina Santos; Fernando José Abelha (Brazilian Journal of Anesthesiology, 2013)
Background and objectives: The Postoperative Nausea and Vomiting (PONV) Intensity Scale was developed to deﬁne clinically important PONV. The aim of this study was to translate, retranslate and validate the PONV Intensity Scale for use in Portuguese Post Anesthetic Care Unit (PACU) settings. Methods: The PONV Intensity Scale was translated and back-translated in accordance with available guidelines. The research team conducted an observational and cohort prospective study in a PACU. One-hundred ﬁfty-seven adult patients admiited after surgery over three weeks were evaluated for PONV. Measurements included nausea visual analogic scale (VAS) at 6 and 24 hours, postoperatively. We assessed reliability and observer disagreement using interclass correlation (ICC) and Information-Based Measure of Disagreement (IBMD). We compared VAS scores between patients with clinically signiﬁcant (≥50) and not signiﬁcant (<50) PONV. Results: Thirty-nine patients (25%) had PONV at 6 hours and 54 (34%) had PONV at 24 hours. Thirty-six and 54 patients experienced nausea at 6 and 24 hours, respectively. Among patients with PONV, 6 patients (15%) and 9 patients (27%) had a clinically signiﬁcant PONV intensity scale score at 6 and at 24 hours, respectively. The reliability was good both for PONV intensity scale score and for VAS and observer disagreement was slightly higher for VAS. The median nausea VAS scores were higher in patients with clinically signiﬁcant PONV Intensity score. Conclusions: The PONV Intensity Scale appears to be an accurate and reliable assessment and monitoring instrument for PONV in the PACU settings. Keywords: Postoperative Care, Postoperative Nausea and Vomiting, Questionnaires, Recovery Room